Synthesis of TiO2−SiO2−Ag/fiberglass with antibacterial properties and its application for air cleaning - Buzaev, Aleksandr A.; Lyutova, Ekaterina S.; Tkachuk, Valeriya A.; Borilo, Lyudmila P.; Chen, Yu-Wen (ACS Omega)
The TiO2−SiO2−Ag/fiberglass with antibacterial properties under UV light irradiation was synthesized. The effects of compositions of TiO2−SiO2−Ag/fiberglass, optical, and textural characteristics on the antibacterial activity were studied. The TiO2−SiO2−Ag film was coated on the surface of fiberglass carrier filaments. The temperature effect on the formation of the TiO2−SiO2−Ag film was established by thermal analysis, and the temperature treatment mode was selected as 300 °C for 30 min, 400 °C for 30 min, 500 °C for 30 min, and 600 °C for 30 min. The influence of silicon oxide and silver additives on the antibacterial properties of TiO2−SiO2−Ag films was established. Increasing the treatment temperature of the materials up to 600 °C increased the thermal stability of the titanium dioxide anatase phase, while the values of optical characteristics decreased: the film thickness decreased to 23.92 ± 1.24 nm, the refractive index decreased to 2.154 ± 0.002, the energy of the band gap width decreased to 2.8 ± 0.5, and the light absorption shifted to the visible-light regime, which is important for photocatalytic reactions. The results showed that the use of TiO2−SiO2−Ag/fiberglass allows significant decrease in the value of CFU microbial cells to 125 CFU m−3.